Overexpression of c-myc in pancreatic cancer caused by ectopic activation of NFATc1 and the Ca(2+)/calcineurin signaling pathway - Buchholz, Malte (2006)
The nuclear factor of activated T cell (NFAT) proteins are a family of Ca(2+)/calcineurin-responsive transcription factors primarily recognized for their central roles in T lymphocyte activation and cardiac valve development. We demonstrate that NFATc1 is commonly overexpressed in pancreatic carcinomas and enhances the malignant potential of tumor cells through transcriptional activation of the c-myc oncogene. Activated NFATc1 directly binds to a specific element within the proximal c-myc promoter and upregulates c-myc transcription, ultimately resulting in increased cell proliferation and enhanced anchorage-independent growth. Conversely, c-myc transcription and anchorage-dependent and -independent cell growth is significantly attenuated by inhibition of Ca(2+)/calcineurin signaling or siRNA-mediated knock down of NFATc1 expression. Together, these results demonstrate that ectopic activation of NFATc1 and the Ca(2+)/calcineurin signaling pathway is an important mechanism of oncogenic c-myc activation in pancreatic cancer.